1997
DOI: 10.1007/s004200050226
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial hyperresponsiveness and exposure in pig farmers

Abstract: Please be advised that this information was generated on 2018-05-09 and may be subject to change.Int Arch Occiip Environ Health (1997) Abstract Objective: To study the effect of exposure on bronchial responsiveness in pig farmers. Method: A group of 196 pig farmers were tested for lung function and bronchial responsiveness to histamine in the sum mer of 1992. To achieve sufficient contrast in respira tory morbidity and exposure, 96 of the farmers were selected because they had chronic respiratory symp toms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
2
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 40 publications
2
43
2
2
Order By: Relevance
“…These include pig farming [Vogelzang et al, 1997], coal mining [Hudgel and Roe, 1988], firefighting [Sherman et al, 1989], obesity [Chinn et al, 2002;Litonjua et al, 2002], chronic lymphocytic leukemia [Rolla et al, 1993], vocal cord dysfunction [Perkins and Morris, 2002], gas cooking [Kerkhof et al, 1999], inhalational drug abuse [Tashkin et al, 1993;Boto de los Bueis et al, 2002], endotoxins , traumatic spinal cord injury [Dicpinigaitis et al, 1994], antishock trousers [Regnard et al, 1990], dietary factors [Soutar et al, 1997], mastocytosis [Mochizuki et al, 2002], human immunodeficiency virus infection [Poirier et al, 2001], tuberculosis [Park et al, 1989], Chlamydia pneumoniae and Chlamydia trachomatis [Bjornsson et al, 1996]; family history [Koh et al, 1998], and a history of severe perinatal respiratory infections [Vonk et al, 2004]. A common pathophysiological mechanism for BHR in this diverse group is not readily apparent, although many of the conditions may be associated with varying degrees of airway inflammation.…”
Section: Miscellaneousmentioning
confidence: 99%
“…These include pig farming [Vogelzang et al, 1997], coal mining [Hudgel and Roe, 1988], firefighting [Sherman et al, 1989], obesity [Chinn et al, 2002;Litonjua et al, 2002], chronic lymphocytic leukemia [Rolla et al, 1993], vocal cord dysfunction [Perkins and Morris, 2002], gas cooking [Kerkhof et al, 1999], inhalational drug abuse [Tashkin et al, 1993;Boto de los Bueis et al, 2002], endotoxins , traumatic spinal cord injury [Dicpinigaitis et al, 1994], antishock trousers [Regnard et al, 1990], dietary factors [Soutar et al, 1997], mastocytosis [Mochizuki et al, 2002], human immunodeficiency virus infection [Poirier et al, 2001], tuberculosis [Park et al, 1989], Chlamydia pneumoniae and Chlamydia trachomatis [Bjornsson et al, 1996]; family history [Koh et al, 1998], and a history of severe perinatal respiratory infections [Vonk et al, 2004]. A common pathophysiological mechanism for BHR in this diverse group is not readily apparent, although many of the conditions may be associated with varying degrees of airway inflammation.…”
Section: Miscellaneousmentioning
confidence: 99%
“…20,21,31 We used nonparametric models to investigate the shape of the dose-response relationship between endotoxin exposure and chronic respiratory symptoms, AHR, and lung function, adjusting for age, smoking habits, and standing height (lung function only). Endotoxin exposure was associated with increased AHR and lower FEV 1 but not with the presence of chronic respiratory symptoms (Fig 3).…”
Section: Respiratory Health Effectsmentioning
confidence: 99%
“…Epidemiological studies of workers exposed to organic dust have shown that respiratory symptoms occur in a wide range of professions where people are exposed to dusts contaminated with microorganisms and their endotoxins (Douwes et al, 1997;Vogelzang et al, 1997;Iversen et al, 1989;Iversen and Pedersen, 1990;Hollander et al, 1994;Milton et al, 1995;Hagmar et al, 1990). These studies have revealed a range of different risk factors for respiratory diseases in the organic dust, from allergens to endotoxins stemming from the ubiquitous microorganisms thriving in these surroundings.…”
Section: Health and Comfortmentioning
confidence: 99%